Sosialisasi Pemeliharaan Alat Kesehatan Timbangan Bayi Pada Posyandu Petunjuk Kalbu Kelurahan Sukajadi - Romi Mulyadi; Albirruni Siregar; Nursaka Putra; Nadia Angelin; Fajar Kurniawan (Abdimas Universal, 2024)
Maintenance and calibration of medical devices tend to only be carried out when facing health center accreditation. This activity has not been carried out in a planned and continuous manner. Lack of socialization, limited distribution of personnel, and the number of calibration laboratories that do not meet the requirements. The target of community service is the Posyandu Petunjuk Kalbu which is a community health service located in Gang Dahlia, Sukajadi Village, where this posyandu group does not understand and know how to calibrate medical devices and has not been exposed to how to repair, maintain and calibrate internal medical devices. The method of community service activities is carried out by presenting materials, calibration practice activities, and reviewing the results of socialization activities, maintenance in the form of repairs and calibration of equipment, especially on baby scales. So that the community needs to be socialized about the management of care and use of medical devices on baby scales. The results of community service activities at the Posyandu Petunjuk Kalbu, cadres and the community were able to understand and know very well, as evidenced by the provision of pretest questions and posttest questions as many as 10 questions, where after the provision of materials the community was able to answer correctly from the 10 questions given with the highest answer value on question number 7 as many as 29 people. With the implementation of this community service, it is hoped that the posyandu cadres will have a good understanding of the repair and calibration of baby scales.